Influence of Cognitive Style and Gender on Secondary School Students’ Achievement in and Attitude to Chemistry - Idika, Mabel. I. (Advances in Social Sciences Research Journal, 2017)
The purpose of the study was to determine the influence of two major cognitive styles (Field Dependent and Field independent) and gender on students’ achievement in and attitude to chemistry. A total of two hundred and eight (208) SSII chemistry students drawn from some selected secondary schools in three local government areas in Ibadan, Oyo state, Nigeria participated in the study. Three instruments were employed in this research. They are Cognitive Style Checklist (r=0.84), Chemistry Achievement Test(r=0.81) and Students’ Attitude to Chemistry Questionnaire(r=0.84) This was a survey research. Four hypotheses were tested at 0.05 level of significance and data collected were analyzed using Descriptive Statistics and t-test. The results showed that there was significant main difference between on field dependent and field independent students’ achievement in chemistry (t(1,207) = 5.173; P < 0.05]; students with field independent level of cognitive style obtained higher mean score of chemistry achievement (= 8.89) than those with field dependent level of cognitive style (= 8.19); there was no significant main difference between field dependent and field independent students’ attitude to chemistry [t(1,207) = 1.271; P>0.05] ; there was no significant main difference between male and female students’ achievement in chemistry [t(1,207) = .704; P>.05] but the female students obtained higher mean achievement score (= 98.64) than their male counterparts (= 98.28); there was significant main difference between male and female students’ attitude to chemistry [t(1,207) = 18.041; P<0.05] Cognitive style can affect students’ achievement in chemistry and those of the field independent category perform better than those of the field dependent category; whereas, cognitive style has no influence on students’ attitude to chemistry. Even though, male and female students do not differ much in their achievement in chemistry, their attitude of the female students to chemistry is better than that of the male students Therefore, it is recommended that teachers have adequate knowledge of the dominant cognitive style category in their classes as this could facilitate and ensure more meaningful learning as well as serve as guide for selection of teaching methods. In addition, chemistry teachers should make efforts in ensuring that chemistry classes are interesting and appealing to their male students.